2009
DOI: 10.1073/pnas.0905815106
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of MyD88-dependent signaling by IL-10 in dendritic cells

Abstract: IL-10 produced by dendritic cells (DC) can limit or terminate ongoing inflammatory responses by inhibiting the proinflammatory cytokine production. Currently, the molecular mechanism by which IL-10 suppresses cytokine production is still ill-defined. In this study, we showed that IL-10 produced by DC dampens myeloid differentiation factor (MyD)88-dependent, but not MyD88-independent signaling. At the molecular level, IL-10 induces ubiquitination and subsequent protein degradation of MyD88-dependent signaling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 27 publications
6
100
0
1
Order By: Relevance
“…1B). IL-10 negatively regulates cytokine production in DC upon LPS stimulation (18). We tested therefore whether IL-10 participates in the inhibition of IL-23p19 gene expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). IL-10 negatively regulates cytokine production in DC upon LPS stimulation (18). We tested therefore whether IL-10 participates in the inhibition of IL-23p19 gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Cytokine concentrations in supernatants were detected by ELISA and mRNA accumulation of cytokines was analyzed by qRT-PCR as previously described (33). The primers used for GAPDH, IL-12p35, IL-12p40, IL-10, IL-6, and IL-23p19 were described previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…In this line, it has been demonstrated that adjuvants not only determine IL-10 production by DC, but also dictate their sensitivity to be inhibited by IL-10, modulating thus their functional properties. 39 Indeed, MyD88-independent adjuvants such as poly(I: C), are resistant to IL-10 inhibitory effects, whereas DC activated through MyD88-dependent adjuvants (Imiquimod or CpG) can be inhibited by this cytokine. Thus, these results may suggest DC as a potential IL-10 source and at the same time may explain why anti-IL-10R antibodies, even in the presence of tumor IL-10, do not provide any benefit when using poly(I: C) or anti-CD40 as adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that an in vivo LPS challenge induces hyporesponsiveness to following in vivo or ex vivo LPS challenges. The biochemical mechanisms accounting for this hyporesponsiveness have been demonstrated to involve negative regulators such as IRAK-M, SOCS-1, SHIP, ST2 and IL-10 [2,3,[12][13][14][15][16][17][18] and downregulation of CD14 [19].…”
Section: Introductionmentioning
confidence: 99%